Clinical behavior - ethiologic of the syncope in patient pediatric - Amarales, Dra. Idalia Morell; Rodríguez, MCs. Dalyla Alonso; Cuesta, MCs. Niurka González (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
the syncope constitutes a complex problem that requires of a clinical guide thathe/she rationalizes it. In the last years it is bigger the interest for the handling ofdifferent causes due to their frequency, nature incapacitante, their potentialgraveness and to the complex problems implied in their genesis and difficult todiagnose. He/she was carried out a study in 80 patients assisted in the externalconsultation of cardiology, of the Policlínic of Pediatric Specialties, and comingfrom the area of hospitalization. the prematuried antecedent is not picked up asfactor to predispose you in the revised literature and this could keep relationshipwith the síncope. In relationship to the cianosis this aspect it was not significant,the same as the apnea crises and the ventilation mechanics in the stageneonatal, however the antecedent of infections was outstanding following himthe hipoxia, the first floor weight when being born and the slowed intra-uterinegrowth. A bigger incidence of the syncope is reported in patient with relativesthat suffer of arterial hypertension. The sudden death in spite of constituting afactor to predispose you very important, it reports few cases since in this studythey are not frequent such cases. He/she was a bigger factors begined like thefear, the pain and the maintained stress, this last one mainly in the adolescents.Most of the patients presented syncopes of vasovagal etiology. Other lessfrequent causes those of origin psicogen, neurological, heart, endocrine and bydrugs. the glucemia levels and hemoglobin in most of the cases stayed in theirnormal values.